2017
DOI: 10.1080/15459624.2017.1350786
|View full text |Cite
|
Sign up to set email alerts
|

Salivary cortisol and alpha-amylase: Is there consistency between psychosocial stress test and burdensome work shifts?

Abstract: This study examined the consistency of salivary cortisol and alpha-amylase (sAA) total daily secretion between laboratory and field circumstances. The 95 participants were shift working female health care professionals with high (n = 53) or low (n = 42) psychosocial stress (job strain) measured by the Job Content Questionnaire (JCQ). The Trier Social Stress Test including a 5-min free speech and a mental arithmetic task was conducted with four, and field measurements with three daily saliva samples of cortisol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
2
0
2
Order By: Relevance
“…From a theoretical perspective, our findings may reveal why numerous inconsistencies in SRS literature exist (Altemus et al, 2001;Balodis et al, 2010;Cacioppo et al, 1998;Engert et al, 2011;Karhula et al, 2017;Khoury et al, 2020;Kudielka et al, 2004;Laurent et al, 2016;Looser et al, 2010;Maruyama et al, 2012;Myers et al, 2017;Nater et al, 2006;Quas et al, 2014;Rahal et al, 2020;Smeets, 2010;Valentin et al, 2015;Weber et al, 2010). Not only is it vital to consider the entire HPA response trajectory (to account for significant covariation in cortisol reactivity, peak, and recovery), but a multisystem approach using indices across SRS is needed as significant relationships between two systems disappear when accounting for the combined interactions across all three systems.…”
Section: Multi-system Stress Coordinationmentioning
confidence: 89%
See 1 more Smart Citation
“…From a theoretical perspective, our findings may reveal why numerous inconsistencies in SRS literature exist (Altemus et al, 2001;Balodis et al, 2010;Cacioppo et al, 1998;Engert et al, 2011;Karhula et al, 2017;Khoury et al, 2020;Kudielka et al, 2004;Laurent et al, 2016;Looser et al, 2010;Maruyama et al, 2012;Myers et al, 2017;Nater et al, 2006;Quas et al, 2014;Rahal et al, 2020;Smeets, 2010;Valentin et al, 2015;Weber et al, 2010). Not only is it vital to consider the entire HPA response trajectory (to account for significant covariation in cortisol reactivity, peak, and recovery), but a multisystem approach using indices across SRS is needed as significant relationships between two systems disappear when accounting for the combined interactions across all three systems.…”
Section: Multi-system Stress Coordinationmentioning
confidence: 89%
“…Pulopulos et al found that decreases in stress‐related anticipation HRV were related to cortisol increases, but not recovery (Pulopulos et al, 2018). Yet, many other studies find no relationship between HRV and cortisol (Altemus et al, 2001; Heilman et al, 2008; Looser et al, 2010) nor cortisol and sAA (Altamura et al, 2018; Karhula et al, 2017; Nater et al, 2006; Valentin et al, 2015) across stress. In studies utilizing the Trier Social Stress Test (TSST: a popular laboratory psychosocial stressor), some findings showed cortisol output significantly related to decreased HRV, while others found no relationship at all (Giles et al, 2014; Laurent et al, 2016; Marques et al, 2010; Rotenberg & McGrath, 2016).…”
Section: Introductionmentioning
confidence: 97%
“…Atualmente, diversas pesquisas relacionadas ao estresse em seres humanos utilizam nas suas investigações biomarcadores fisiológicos, sendo o cortisol salivar mencionado com maior frequência [5][6][7][8]. Não obstante, estudos que objetivam a mensuração do estresse também são frequentemente realizados com instrumentos validados [9][10][11].…”
Section: Introductionunclassified
“…Até o momento, não se conhece o papel do hipocortisolismo na etiologia da fadiga ocupacional. Porém, em virtude da importância do cortisol no metabolismo energético e de sua relação com a fadiga em populações clínicas (POWELL et al, 2013;KALLESTAD et al, 2015;TECHERA et al, 2016;MILRAD et al, 2017) (CLOW et al, 2010;STALDER et al, 2017;KARHULA et al, 2017 Esta pesquisa tem por finalidade avaliar o estresse ocupacional dos trabalhadores enfermeiros submetidos ao trabalho em turnos fixos noturnos e diurnos e a concentração de cortisol e sua possível associação com estressores ocupacionais.…”
Section: Considerações Sobre Os Níveis De Cortisol Salivarunclassified